Photoaging Skin Therapy with PRP and ADSC: A Comparative Study - Luiz Charles-de-Sá; Natale Gontijo-de-Amorim; Andrea Sbarbati; Donatella Benati; Paolo Bernardi; Radovan Borojevic; Rosana Bizon Vieira Carias; Gino Rigotti (Stem Cells International)
Background. Stem cells from adipose tissue (ADSCs) and platelet-rich plasma (PRP) are innovative modalities that arise due to their regenerative potential. Objective. The aim of this study was to characterize possible histological changes induced by PRP and ADSC therapies in photoaged skin. Methods. A prospective randomized study involving 20 healthy individuals, showing skin aging. They underwent two therapeutic protocols (protocol 1: PRP; protocol 2: ADSCs). Biopsies were obtained before and after treatment (4 months). Results. PRP protocol showed unwanted changes in the reticular dermis, mainly due to the deposition of a horizontal layer of collagen (fibrosis) and elastic fibers tightly linked. Structural analyses revealed infiltration of mononuclear cells and depot of fibrotic material in the reticular dermis. The ADSC protocol leads to neoelastogenesis with increase of tropoelastin and fibrillin. There was an improvement of solar elastosis inducing an increment of macrophage polarization and matrix proteinases. These last effects are probably related to the increase of elastinolysis and the remodeling of the dermis. Conclusions. The PRP promoted an inflammatory process with an increase of reticular dermis thickness with a fibrotic aspect. On the other hand, ADSC therapy is a promising modality with an important antiaging effect on photoaged human skin.